The Impact of Perceived Ease, Usefulness, and Risk on Decisions to Use Brimo QRIS (Case Study in Central Java and Implications for Management) - Prasetyo, Bowo; Wahyudi, Tri Nur (Ilomata International Journal of Management, 2025)
Digital payment transactions and the widespread use of electronic devices are hallmarks of the cashless society that is emerging in tandem with the Fourth Industrial change and the change in financial technology. This study aims to examine how people in Central Java perceive the ease, benefits, and hazards of using QRIS, and how these factors influence their decision-making process. This study used a casual associative design and was quantitative in nature. This study used purposive sampling, which selects a population subset according to norms. One hundred people participated in this study. This study included multiple linear regression, hypothesis testing, classical assumption testing, and instrument testing. With a simultaneous test value of 70.201 and a Ftable value of 2.70, along with partial test values of the three variables exceeding the t table value of 1.986, this study concludes that perceptions of convenience, benefits, and risk significantly impact the decision to use BRImo QRIS in Central Java.